Islamic Banking as an Alternative to Banks in the Western Countries - Lakis, Vaclovas; Baltušytė, Daiva (Ekonomika, 2018)
After the last banking crisis in the Western world, which provoked an economic recession in many countries, the attention to Islamic banking has increased. Islamic banking took a more important place in global banking, since the economic and financial crisis there was of smaller scope than in the banks of Western countries.The principles of Islamic banking are based on Shariah requirements, which emerged from the Koran. The most important fact is that Islamic banks cannot seek profit, which does not require any risk or efforts. They do not use any financial instruments, which are not covered by assets (derivatives). On the other hand, Islamic banks, while granting loans, assume all or a part of risk, if in the case of implementation of project some losses appear. They responsibly appreciate the possibility of granting the loans, the main goal of which is to finance projects and promote business development; they share the risk with the clients and value mutual cooperation.The goal of the article is to investigate the peculiarities of Islamic banking. The article investigates the formation of Islamic banking’s main characteristics and principles, its accounting peculiarities and the instruments that are applied.Research methods include the analysis of collected information, comparison, critical assessment and induction.
Keywords: Islamic banking; Shariah requirements; banking principles; banking products; corporate social responsibility